Nouvelles recherches sur une trilogie pastorale d'Augustin ( s. 133, Dolbeau 10 [162 C], 89) - Dolbeau, François (Augustiniana, 2025)
This article expands on a study published in Augustiniana 66 (2016), p. 7-62. The three sermons concerned form a trilogy dedicated to proving the veracity of divine Scriptures. They were preached outside Hippo Regius, at the beginning of Augustine’s episcopate, probably in Carthage. Contrary to the direct tradition of the trilogy, the indirect tradition is considerable, and excerpts copied in Catalonia, inside a canonical collection, make it possible to improve the text of Sermo Dolbeau 10 (162C).